Long-Range Charge Reorganization as an Allosteric Control Signal in Proteins - Banerjee-Ghosh, Koyel (J Am Chem Soc, 2020)
[Image: see text] A new mechanism of allostery in proteins, based on charge rather than structure, is reported. We demonstrate that dynamic redistribution of charge within a protein can control its function and affect its interaction with a binding partner. In particular, the association of an antibody with its target protein antigen is studied. Dynamic charge shifting within the antibody during its interaction with the antigen is enabled by its binding to a metallic surface that serves as a source for electrons. The kinetics of antibody–antigen association are enhanced when charge redistribution is allowed, even though charge injection happens at a position far from the antigen binding site. This observation points to charge-reorganization allostery, which should be operative in addition or parallel to other mechanisms of allostery, and may explain some current observations on protein interactions.